Former Priest faces lawsuit Sex abuse alleged in federal case - Simon, Russell Max (Raton, New Mexico Raton Range, 2006)
Article on local Priest facing a lawsuit on alleged sexual abuse case.
Master list item #: 6
File location is in the Raton File Cabinet
Keywords: Sheehan, Michael; Silva, George; Radigan, Celine; Trespel,Jeffrey; Archdiocese; U.S. District Court; St. Patrick's/St. Joseph's Church; FBI; Local History; Churches; Priest; Sexual Abuse; Archdiocese; Investigation; Raton, New Mexico; Santa Fe, New Mexico; Albuquerque, New Mexico; Portugal